IMPLEMENTAÇÃO DE PROTOCOLO DE UTILIZAÇÃO DE CORTICOSTEROIDE NO CHOQUE SÉPTICO PEDIÁTRICO - Ilha, Jean Pierre Paraboni (2017)
High mortality rates are related to pediatric sepsis. Literature is limited on corticosteroid use context in pediatric septic shock, as in article numbers as in methodological quality of studies. The non-padronization for the beginning of this drug use is indicated as the main reason of discrepancy of studies results, and it can be one of the associated factors in mortality in this clinical situation. Based on this problem question, the present study had as general objective to systematize the corticosteroid utilization in cathecolamine resistant pediatric septic shock in a pediatric unity care of an education hospital. As specific objectives, this study considered: to make a bibliographic review on pediatric sepsis aiming the recent management of pediatric septic shock, and to capacitate the local medical staff for the application of corticosteroid utilization protocol in pediatric septic shock, monitoring its application on indicated children. In order to attending the first specific objective, it was made a bibliographic state-of-art review in children sepsis, with resources in internation data base Pubmed and Lilacs. The resulting date from the first specific objective resulted in a book chapter where it was inserted this knowledge, and also as theorical basis for protocol construction for corticosteroid use in the indicated moment in pediatric septic shock. It was concluded that this review, for punctuating the right moment of this drug utilization, aims to contribute to the management of the referred disease, With the purpose of systematizing the conducts and qualifying the professionals' performance, in this process. The second specific objective was about an action-research, involving the protocol construction process of corticosteroid utilization in cathecolamine resistant pediatric septic shock, matching to a specific part of the time sensitive algorithm for management of pediatric septic shock, internationally validated, and the capacitation of the medical staff from the referred unity for its utilization, in the period of june, 2016. From the result data of the second specific objective, and codificated on content analysis, three thematic categories were resulted: previous learning of protocol for treatment of the referred shock, positive actions associated to assistential protocols using in intensive care unities and continued education in these places. After effective medical capacitation there was utilization of this drug from systematic manner in 100% of the patients under this clinical condition, in a six-month period after capacitation, showing that the final product of this work had a good internal validity. With this optimization there is possibility of local future studies of clinical ending.